Banks and markets in the financial service industry: are their roles complementary or competitive in Nigeria?. (2017) - Arize, Augustine C.; Kalu, Ebere Ume; Nkwor, Nelson Nwani
Empirical investigations on the financial structure of most economies have largely focused on the superiority of financial services offered banks or capital markets as well as at what stage of economic development of such economies do these respective services predominate. There is, however, a departure in the debate from the interplay between banks and markets in financial service offering to complementary or otherwise of these relationships in an economy. This paper explores the relationship between banks and stock markets, whether they compete or complement each other in the context Nigerian financial system. The study found a complementary rather than competing relationship, which suggests a co-evolving development in the Nigerian financial structure and financial service offering. It is, therefore, recommended that concerted efforts should be directed towards action-based approaches in the development of both Nigerian banking and capital markets for a rapid and collaborative development in the financial system, which in no small measures would drive enhanced financial service offering, financial inclusion and ultimately economic growth.